Bits and pieces eaudiobook My mother, my brother, and me. - Goldberg, Whoopi (Blackstone Publishing, 2024)
An instant New York Times and USA Today bestseller! From multi-award winner Whoopi Goldberg comes a new and unique memoir of her family and their influence on her early life. If it weren't for Emma Johnson, Caryn Johnson would have never become Whoopi Goldberg. Emma gave her children the loving care and wisdom they needed to succeed in life, always encouraging them to be true to themselves. When Whoopi lost her mother in 2010—and then her older brother, Clyde, five years later—she felt deeply alone; the only people who truly knew her were gone. Emma raised her children not just to survive, but to thrive. In this intimate and heartfelt memoir, Whoopi shares many of the deeply personal stories of their lives together for the first time. Growing up in the projects in New York City, there were trips to Coney Island, the Ice Capades, and museums, and every Christmas was a magical experience. To this day, she doesn't know how her mother was able to give them such an enriching childhood, despite the struggles they faced—and it wasn't until she was well into adulthood that Whoopi learned just how traumatic some of those struggles were. Fans of personal memoirs such as Finding Me by Viola Davis and In Pieces by Sally Field will be touched by Bits and Pieces: a moving tribute from a daughter to her mother, and a beautiful portrait of three people who loved each other deeply. Whoopi writes, "Not everybody gets to walk this earth with folks who let you be exactly who you are and who give you the confidence to become exactly who you want to be. So, I thought I'd share mine with you."